Igrejinha da Pampulha: descritivo histórico das intervenções e estado de conservação atual - Otavio Augusto de Sa Starling (2018)
The Curial Chapel São Francisco de Assis is an example of crucial importance of the modern architectural patrimony, registered in all of the spheres of protection in Brazil and recognized by UNESCO as a humanitys patrimony.Constructed from 1942 to 1945, it passed by several interventions in the years 1954, 1957, 1980, 1990-1992 and 2004-2005, with the main objective of solving the damages associated with the physical degradation of the surfaces and structure of reinforced concrete. This work, with a qualitative approach and exploratory character, has as main objective the descriptive historical of the interventions focusing on the questions linked to the current state of conservation for a better understanding of the problem of structural dilation. It intends to subsidize more rigorous criteria and guidelines in a forthcoming intervention and to foment the debates about the conservation of the modern architectural patrimony.